Study on the effects of milling time and sintering temperature on the sinterability of forsterite (Mg2SiO4) - Tan Y.M.; Tan C.Y.; Ramesh S.; Teh Y.C.; Ching Y.C.; Lwin N.; Yap B.K.; Agrawal D. (Ceramic Society of Japan, 2023)
Bioceramics; Crystallite size; Fracture toughness; Heat treatment; Milling (machining); Olivine; Powders; Sintering; Solid state reactions; Temperature; X ray diffraction; X ray powder diffraction; Effects of temperature; Forsterite powder; Forsterites; Heat treatment temperature; Optimum conditions; Relative density; Sinterability; Sintering temperatures; Ball milling